The role of Nigerian agriculture in West African food security - Babatunde, Raphael O. (International Food Policy Research Institute, 2012)
The main objective of this study is to examine the role of Nigerian agriculture in West African food security. The study discusses the implications of Nigeria’s agricultural production, the potentials for Nigerian export of agricultural products to enhance regional food security, and the role that the Comprehensive Africa Agriculture Development Program (CAADP) could play in supporting agricultural research and development (R&D) efforts in the region.